Evolution characteristics and mechanisms of the spring warm pool in the Bay of Bengal - Lin, Wenshu; Qiu, Yun; Ni, Xutao; Lin, Xinyu; Liu, Tongtong (Frontiers in Marine Science, 2024)
In this study, we investigate the spatial structure and evolution of the spring warm pool in the Bay of Bengal (BoBWP) using daily Optimum Interpolation sea surface temperatures (SST) data from 1982-2022 in combination with multi-source data. Our analysis shows that the BoBWP is located in the central bay (6°-13°N) with a thickness around 20 m 40 m. Composite analysis indicates that the BoBWP emerges in early April, peaks in early May and dissipates in early June. During the developing period, the net heat flux dominates the formation of spring warm pool through a significant air-sea coupling processes, and induces the warming rate of 0.31 ℃/10d in the mixed layer, which is far larger than the contribution of oceanic dynamical processes (0.02 ℃/10d). During the decaying period, the net heat flux also plays a dominant role, with a cooling rate of -0.11 ℃/10d, meanwhile ocean dynamical processes contribute to the cooling of the warm pool with a rate of -0.02 ℃ /10d. Additionally, the SST and area of the BoBWP are significantly correlated with ENSO (r=0.66 and 0.73, p=0.05). During El Niño decaying year, the BoBWP primarily expands in a southward, with a 75% increase in area. Conversely, during La Niña decaying year, the BoBWP almost disappears, with a 52% decrease.